2012
DOI: 10.1080/09853111.2013.839126
|View full text |Cite
|
Sign up to set email alerts
|

Nature and onset age of neotectonic regime in the northern core of Isparta Angle, SW Turkey

Abstract: The Isparta Angle (IA) is a reverse Λ-shaped morphotectonic structure located to the north of Antalya Gulf in the Eastern Mediterranean Sea. It resulted from the northward curvature of the originally E-W-trending Tauride orogenic belt owing to the nappe emplacements and related clockwise and anti-clockwise rotations in a time period of Early Paleocene to Early Pliocene. The IA is included in the southwest Anatolian tensional neotectonic domain and characterized by a series of grabens and horsts bounded by acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…They claimed that the Yarıkkaya Formation was deformed by this short compressive tectonic episode. The field observations presented in Koçyiğit et al (2012) and also in our study show that folds developed in the Yarıkkaya Formation are only very gentle (interlimb angles are between 180° and 120°). This type of undulations can easily develop during extension al tectonic regime (Schlische 1995).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…They claimed that the Yarıkkaya Formation was deformed by this short compressive tectonic episode. The field observations presented in Koçyiğit et al (2012) and also in our study show that folds developed in the Yarıkkaya Formation are only very gentle (interlimb angles are between 180° and 120°). This type of undulations can easily develop during extension al tectonic regime (Schlische 1995).…”
mentioning
confidence: 91%
“…14) show that its motions are consistent with basin extension. Koçyiğit et al (2012) concluded that extension shaped the Yalvaç Basin, interrupted by a short-term contractional phase. They claimed that the Yarıkkaya Formation was deformed by this short compressive tectonic episode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This deformation pattern is seen obviously in Kuşadası and Söke areas located at the westernmost tip of the Büyük Menderes Graben (Gürer et al, 2001), in the Halitpaşa graben (Kaya et al, 2004), along the northern margin of the Kiraz half graben located at the eastern tip of the Küçük Menderes graben (Bozkurt & Rojay, 2005), in the Künüpe section of the Büyük Menderes detachment fault zone, to the northeast of Kızıldere settlement located north-eastern margin of the Büyük Menderes Graben (Şimşek, 1985), around Acıdere village located on the southern slope of the Çökelezdağ which comprises the Çivril Graben (Koçyiğit, 2013b), in the apex of Isparta Angle (Boray, Saroğlu, & Emre, 1985), in the Deresenek section of the Akşehir-Afyon Graben (Koçyiğit, Ünay, & Saraç, 2000) and in the Yenigediz-Erdoğmuş Graben (Kütahya) (Gürboğa, Koçyiğit, & Ruffet, 2013). In addition, older graben fill is always folded in not only the Gediz and Büyük Menderes grabens shaped by the detachment normal fault zone, but also in and outside the whole of rest grabens, which lack detachment fault zones but included in the south-western Turkey neotectonic domain (Bozkuş, 1996;İnci, 1991Koçyiğit, 1983Koçyiğit, , 1997Koçyiğit & Deveci, 2007;Koçyiğit, Gürboğa, & Kalafat, 2013;Koçyiğit, Gürboğa, & Ruffet, 2013;Yağmurlu, 1991).…”
Section: Back-tilted and Folded Graben Fillsmentioning
confidence: 99%
“…The short-term diachronic compressive events, which deformed the older graben fills of dissimilar facies and age range, can be classified into two groups based on their occurrence times and origins: (1) Late Langhian-Messinian compressive events and (2) Late Early Pliocene-Late Pliocene events. The first group of compressive events may be related to the emplacement of the Lycian Nappes onto the Beydağları, which comprises the western limb of the Isparta Angle, and the first phase of Aksu thrusting across the eastern limb of the Isparta Angle (Koçyiğit, Gürboğa, & Kalafat, 2013;Poisson, Wernli, Sagular, & Temiz, 2003). However, the first group of compressive events occurred in Miocene may be the most distinct reflections of the continent-continent collision of the Eurasian and Arabian plates and consequent formation of the Bitlis suture in south-eastern Turkey in late Middle Miocene (Dewey, Hempton, Kidd, Şaroğlu, & Şengör, 1986;Koçyiğit, 2013a;Şengör & Yılmaz, 1981).…”
Section: Back-tilted and Folded Graben Fillsmentioning
confidence: 99%